2021
DOI: 10.3390/cancers13143572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Features of Non-Small Cell Lung Cancer with G12C KRAS Mutation

Abstract: KRAS G12C mutations are important oncogenic mutations that confer sensitivity to direct G12C inhibitors. We retrospectively identified patients with KRAS+ NSCLC from 2015 to 2019 and assessed the imaging features of the primary tumor and the distribution of metastases of G12C NSCLC compared to those of non-G12C KRAS NSCLC and NSCLC driven by oncogenic fusion events (RET, ALK, ROS1) and EGFR mutations at the time of initial diagnosis. Two hundred fifteen patients with KRAS+ NSCLC (G12C: 83; non-G12C: 132) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…4 CNS metastases are observed at diagnosis in 27%-42% of patients with KRAS G12C -mutated NSCLC. [5][6][7][8] Patients with KRAS-mutated NSCLC and CNS metastases have a worse prognosis and higher rates of CNS failure compared with patients without KRAS mutations. [9][10][11] Adagrasib (MRTX849), a KRAS G12C inhibitor that selectively and irreversibly binds the switch II pocket of KRAS G12C , 12 has demonstrated CNS penetration, intracranial (IC) tumor regression, and increased survival in multiple preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…4 CNS metastases are observed at diagnosis in 27%-42% of patients with KRAS G12C -mutated NSCLC. [5][6][7][8] Patients with KRAS-mutated NSCLC and CNS metastases have a worse prognosis and higher rates of CNS failure compared with patients without KRAS mutations. [9][10][11] Adagrasib (MRTX849), a KRAS G12C inhibitor that selectively and irreversibly binds the switch II pocket of KRAS G12C , 12 has demonstrated CNS penetration, intracranial (IC) tumor regression, and increased survival in multiple preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true for research on BM of SCLC and NSCLC. Numerous imaging characteristics of NSCLC have been established based on radionics and machine deep learning 15,16 . However, due to the low incidence of BMs of SCLC, their features have not been comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges in treating this population may have possibly added to their overall poor prognosis. Previous data have shown that patients with KRAS G12C mutations have a lower frequency of lung metastasis than EGFR -positive patients do (38% vs. 67%) and a high prevalence of brain metastases (28% at diagnosis and 40% during follow-up) [ 27 , 29 ]. We found that 28% of the patients had pulmonal and 24% had intracranial metastases at diagnosis of advanced-stage KRAS G12C -mutated NSCLC.…”
Section: Discussionmentioning
confidence: 99%